Enhanced Mechanical Properties of Mortar Reinforced with Recycled and Depolymerized Nylon Microfibers - K. Pilares Aroquipa, Mayra; A. Cumpa Pinedo, Maria; D. Almanza Obregón, Sherlín; R. Pérez, Rodolfo; Salazar Banda, Giancarlo Richard (International Journal of Sustainable Construction Engineering and Technology, 2025)
This study explores the potential of recycled nylon 6 to improve the mechanical properties of mortar modified through chemical additives and the reinforcement of nylon microfibers, referred to as the chemical and physical recycling methods, respectively. The chemical recycling approach involved the depolymerization of nylon into ε-caprolactam monomers, while the physical method utilized recycled nylon microfibers derived from waste. The investigation emphasized evaluating the reinforcement potential of pure depolymerized ε-caprolactam, without other additives, in mortars. Laboratory-produced mortars incorporated these additives, and their flexural, tensile, and compressive properties were meticulously examined. Additives, including the chemical additive ε-caprolactam and nylon microfibers, were incorporated at concentrations of 0.10%, 0.15%, 0.25%, and 0.50% relative to the cement weight. The purity of the depolymerized monomer was verified using Fourier transform infrared spectroscopy analysis. Mechanical tests of the modified mortars (with chemical additive or microfibers) were conducted at 7 and 28 days of curing, to assess the impact of the additives incorporation on the mechanical properties of polymeric mortars. The additive concentration significantly influenced the mortar performance. The optimal compressive strength was achieved with a 0.25% concentration of both chemical additive and microfibers, while tensile strength improved markedly with 0.25% of ε-caprolactam. Similarly, flexural and tensile strengths were maximized with a 0.10% concentration of nylon microfibers. Notably, compressive strength for mortars with 0.25% ε-caprolactam derived from depolymerized nylon waste was comparable to those with commercially sourced monomers. These findings highlight the viability of recycling nylon waste as a sustainable strategy for producing effective additives in polymeric-modified mortars. This approach emphasizes the potential of reusing low-value plastic waste for innovative applications in the civil construction industry.